2020
DOI: 10.1111/jcpe.13249
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic changes at tissue level implants with either a machined or a modified transmucosal neck surface: A 3‐year multicentre randomized controlled proof‐of‐concept study

Abstract: Background Surface modification may yield enhanced soft tissue adhesion to transmucosal titanium implant necks. Aim To evaluate and compare changes in soft tissues around implants with a modified hydrophilic sandblasted and acid‐etched neck (mSLA; test) to those with a machined neck (M; control). Materials and methods Implants with a diameter of 4.1 mm and a neck height of 1.8 mm were randomly inserted in healed sites with pristine bone of the posterior maxilla or mandible. The modified Sulcus Bleeding Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…However, the purpose of this work was first to compare the implant and periodontal status and their associations during implant follow-up. e one-year function was chosen as the minimal follow-up duration requirement for patient inclusion because it allowed a sufficient time for soft peri-implant tissue and bone initial adaptation to the oral environment and for their stabilization to occur [16,56]. Furthermore, this time was frequently chosen in comparable studies [20,21,24,32,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, the purpose of this work was first to compare the implant and periodontal status and their associations during implant follow-up. e one-year function was chosen as the minimal follow-up duration requirement for patient inclusion because it allowed a sufficient time for soft peri-implant tissue and bone initial adaptation to the oral environment and for their stabilization to occur [16,56]. Furthermore, this time was frequently chosen in comparable studies [20,21,24,32,43].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the influence of implant surface topography (i.e., micro and macro design) on the incidence of peri‐implant diseases in humans is still limited 48–51 …”
Section: Peri‐implant Diseases In Humansmentioning
confidence: 99%
“…Based on the hypothesis that surface modification may yield enhanced soft tissue adhesion to transmucosal titanium implant necks, thereby reducing the incidence of peri‐implant diseases, a randomized controlled trial evaluated and compared clinical and radiographic changes at tissue level implants with either a machined or a modified transmucosal neck surface 51 . The outcomes of that study indicated that tissue level implants with a hydrophilic sand‐blasted and acid‐etched transmucosal neck failed to yield clinical and radiographic benefits compared with implants with a machined neck up to 3 years 51 …”
Section: Peri‐implant Diseases In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Implant surface modifications may facilitate enhanced soft-tissue adhesion resulting in clinical and radiographic benefits once implants are exposed to the contaminated environment of the oral cavity. To study this proposed transmucosal benefit, Salvi et al 268 Multiple implant surface modifications have been proposed for the treatment of peri-implantitis, yet none has been identified as most effective. Lasserre et al 269 studied the efficacy of implantoplasty and glycine air polishing for the surgical management of periimplantitis.…”
Section: Peri-implant Disease and Treatmentmentioning
confidence: 99%